AN ASSESSMENT OF THE GRAMMATICAL STRUCTURES AND MECHANICS OF WRITING FACEBOOK POSTS - BABARAN, NILDA O. (International Journal of Psychosocial Rehabilitation, 2020)
Facebook is an imperative means of communication and social interaction. This study which is qualitative in design determined the proficiency of students writing Facebook posts. It looked into the grammatical structures, punctuations and emoji used by the participants. Data were gathered from Facebook posts and were analyzed analyzed using a checklist covering rules of grammar, mechanics and appropriate use of emoticons. The study found out that the Facebooks posts are short but had big images; they are seasonal; they are usually related to business and usually asked questions. Apparently, these kind of posts were the ones usually liked and got the most number of comments. The Facebook posts are also coherent and unified, using proper emoticons, and they express a complete thought, but the use of the emoji stood out among the features. But no matter how well a Facebook user attempts to post an awesome post, they still could not evade errors which led to the conclusion that there are five major weaknesses present in Facebook posts: use of abbreviations, improper capitalization, misused punctuation marks, incorrect spelling, omission of words, wrong diction, and misuse of subject and verb agreement.